AB0429 Clinical manifestations and their association with the immunological profile of primary sjögren's syndrome. (23rd January 2014) - Fernandez Nacul, S.; Secco, A.; Oliver, M.; Gauna, M.; Puente Trigo, D.; Santiago, L.; Catalan Pellet, A.; Velez, S.; Zazzetti, F.; Barreira, J.; Duarte Noe, D.; Pucci, P.; et al.
Abstract : Objectives: 1-Describe the frequency of the clinical manifestations. 2- Assess their association with the antibodies anti Ro/La, ANA, Rheumatoid Factor (RF) in patients with Primary Sjögren's Syndrome (pSS). Methods: It was analyzed the information from the GESSAR's (Argentine Sjögren's Syndrome Group of Study) database of patients diagnosed with pSS according to 2002 American-European criteria. Results: Out of 334 patients, 96% were women, with a median age of 57 (riq: 45-66), a median age at time of diagnosis of 52 (riq: 39-61) and a median age at onset of the symptoms of 47 (riq: 34-57), 95.78% presented xerophthalmia, 93.37% xerostomia, 32.18% parotid gland enlargement, 68.29% arthralgias, 29.58% arthritis, 8.22% purpura, 15.76% Raynaud's disease, 5.41% pulmonary parenchymal affection, 3.60% renal affection, 9.24% peripheral neuropathy, 16.46% anemia of chronic diseases, 13.13% leukopenia and 49.36% polyclonal hypergammaglobulinemia. Anti Ro/anti La + 242/322, ANA + 264/319, RF + 138/299. In univariate analysis anti Ro/La was significantly associated with age (OR 0.98 IC95% 0.96-0.99, p<0.01), age at diagnosis (OR 0.97 IC95% 0.95-0.99, p<0.01), polyclonal hypergammaglobulinemia (OR 4.17 IC95% 1.94-8.96, p<0.01), anemia of chronic diseases (OR 2.53 IC95% 1.10-5.82, p=0.03), ANA (OR 10.93 IC95% 5.50-21.73, p<0.01), RF (OR 2.96 IC95% 1.67-5.23, p<0.01). ANA was associated with age at diagnosis (OR 0.98 IC95% 0.96-0.997, p=0.03), polyclonal hypergammaglobulinemia (OR 3.58 IC95% 1.46-8.76, p<0.01), anti /La (OR 10.93 IC95% 5.50-21.73, p<0.01), RF (OR 3.53. IC95% 1.77- 7.07, p<0.01), and RF was associated with polyclonal hypergammaglobulinemia (OR 2.65 IC95% 1.55-4.54, p<0.01), parotid gland enlargement (OR 1.82 IC95% 1.1-3.01, p=0.02), anemia of chronic diseases (OR 2.24 IC95% 1.17-2.28, p:0.02), Ro/La (OR 2.96 IC95% 1.67-5.23, p<0.01), ANA (OR 3.53 IC95% 1.77- 7.07, p<0.01). In the multivariate analysis, it was found significant and independent association between anti Ro/La and hypergammaglobulinemia (OR 3.37. IC 95% 1.50-7.55, p<0.01), age at time of diagnosis (OR 0.96. IC 95% 0.94-0.99, p<0.01) and ANA (OR 5.59 IC95% 2.25-13.88, p<0.01); the ANA remained associated with anti Ro/La (OR 9.14 IC95% 4.44-18.85, p<0.01) and with RF (OR 2.3 IC95% 1.05-5.04, p:0.04); whereas the RF was associated independently with hypergammaglobulinemia (OR 2.27 IC95% 1.30-3.96, p<0.01) and ANA (OR 4.32 IC95% 1.55-11.99, p<0.01). Conclusions: Sicca symptoms followed by arthralgias were the most frequent clinical manifestations. Hypergammaglobulinemia was the only manifestation significantly and independently associated with seropositivity for anti Ro/anti La antibodies and RF. Disclosure of Interest: None Declared